Successful practices in GIS-based asset management - Hall, James P. (Report (National Cooperative Highway Research Program), 2015)
"TRB's National Cooperative Highway Research Program (NCHRP) Report 800: Successful Practices in GIS-Based Asset Management provides guidance for state transportation agencies on using geographic information system (GIS) technologies in transportation asset management (TAM)."--Publisher's description.